Neonatal Surgery Intensive Care Unit: Hacettepe University Experience - Tandircioglu, Umit Ayse; Celik, Hasan Tolga; Yigit, Sule; Yurdakok, Murat (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVES: Surgical treatment in the neonatal period is very significant. The neonatal surgery intensive care model has been applied in our hospital for about six years. This study aims to examine the data gathered from the neonatal intensive care unit of our hospital and to understand how this model contributed to the health improvement of newborns with surgical problems. STUDY DESIGN: The file records of newborns admitted to the neonatal intensive care unit were retrospectively analyzed from January 2014 to December 2019. The protocol was registered with Clinical Trials.gov identifier NCT04734002. RESULTS: The total number of newborns admitted to the neonatal intensive care unit was 5442. Surgery was performed on 546 of these patients. Two hundred and four patients were hospitalized due to congenital heart disease. Two hundred patients were operated on by pediatric surgeons whereas 142 were operated on by other surgery specialists. In the last six years, the mortality rate was 5.25% in babies without surgical diseases and 18.3% in those with surgical diseases (p<0.05). The hospitalization periods of the babies followed up in our neonatal intensive care unit in the last two years were evaluated. Thereupon, premature babies with other diseases were hospitalized for an average of 9.6 days; however, those patients who require surgery were hospitalized for 33.0 days (p<0.05). The term babies, who did not have any surgical diseases were hospitalized for an average of 4.8 days and those with surgical indications for 16.5 days (p<0.05). CONCLUSION: We believe that the neonatal surgery intensive care unit model should become widespread in Türkiye. We intend to draw attention to this matter through our study, sharing our own experience.